Lymph Node Drainage Patterns and Micrometastasis in Lung Cancer - Kim, Anthony W. (Seminars in thoracic and cardiovascular surgery, 2009)
The basic anatomic lymph node drainage patterns from lung cancers have remained relatively constant since their early descriptions. Sentinel lymph node mapping and other reviews of anatomic resections have provided additional information regarding drainage patterns of lymphatic metastases. In light of these efforts, topics related to lymphatic metastases, such as skip metastasis and micrometastasis, still remain the subject of investigation. A review of the recent literature shows that the incidence of macroscopic skip metastasis is approximately 25%. Despite the occurrence of skip metastases, a generalized lymphatic drainage pattern is observed and is consistent with the drainage patterns that are observed among nonskip metastases to the mediastinum. Direct mediastinal drainage or the inability to detect micrometastatic disease due to observational errors or technical inadequacies may explain the presence of skip metastasis. This is supported by the fact that a review of the recent literature also shows that the incidence of micrometastasis is approximately 19%. The similarities between these 2 values suggest that an improved ability to detect micrometastatic disease is needed. This manuscript reviews the patterns of lymph node drainage from a historical and current perspective to facilitate an understanding of the existing knowledge with respect to skip metastasis and micrometastasis.